Efficient Generator of Structural Topologies Based on Irregular Cellular Automata - Bogdan BOCHENEK; Katarzyna TAJS-ZIELIŃSKA (Engineering Transactions, 2017)
Recent development of Cellular Automata implementation into optimal design problems has shown that the automaton can be an effective tool for generation of optimal topologies in engineering applications. Nevertheless, the vast majority of results have been obtained to date for regular lattices of cells. The aim of the present paper is therefore to extend the concept of Cellular Automata towards irregular grid of cells related to non-regular mesh of finite elements. Introducing irregular lattice of cells allows to reduce number of design variables without losing accuracy of results and without excessive increase of number of elements caused by using fine mesh for a whole structure. This paper proposes a novel Irregular Cellular Automata formulation that can be adapted to topology optimization of real structural elements. The effectiveness of proposed local update rule is illustrated by results of numerical generation of optimal topologies for selected spatial engineering structures.